Genetic diversity and phylogenetic analysis of matoa (Pometia pinnata) from South Sumatra, Indonesia based on ITS rDNA - LAILA HANUM; SALWA GHANIYU USMAN; YADI OKTARIANSYAH (Society for Indonesian Biodiversity, 2025)
Abstract. Hanum L, Usman SG, Oktariansyah Y. 2025. Genetic diversity and phylogenetic analysis of matoa (Pometia pinnata) from South Sumatra, Indonesia based on ITS rDNA. Biodiversitas 26: 5515-5524. Matoa (Pometia pinnata) is an ecologically and economically significant tropical fruit tree, however, its genetic variation in South Sumatra, Indonesia remains poorly characterized. This study aimed to examine the genetic diversity and phylogenetic relationships of four matoa variants, i.e., red, yellow, green, and forest types using ITS rDNA sequences. PCR amplification yielded sequences of 681 bp for cultivated and 478 bp for forest matoa, revealing two InDel haplotypes, 141 InDel sites, and three InDel events with moderate haplotype diversity (Hd = 0.50) and low InDel diversity per site (?i = 0.001). These findings indicate limited but informative structural variation linked to insertion-deletion mutation events, supporting the ITS region’s dual role as both a conserved barcode and a marker for intraspecific differentiation. Phylogenetic and AMOVA analyses showed clear separation between cultivated and forest variants, with almost all genetic variation (99.9997%) partitioned among populations (Fst = 0.999997), suggesting restricted gene flow and possible ecological divergence. Despite high sequence similarity of 99.85% to 100% confirming conspecificity, forest matoa formed a distinct clade and grouped separately, highlighting its potential as a unique genetic reservoir. These results provide foundational molecular insights for conservation, breeding, and germplasm authentication strategies for matoa in Indonesia.